1969
DOI: 10.1177/003693306901400203
|View full text |Cite
|
Sign up to set email alerts
|

Negative Association between Allergy and Cancer

Abstract: In a survey of 140 patients in the gynaecology wards of a large general hospital, the subjects were asked whether they suffered from any of the common hay-fever type allergies, for example, to flowers, bedding dust, etc. An incidence of 20 per cent was established. Surgical and biopsy reports on this ward population established an incidence of malignant conditions at 28 per cent. These two groups of comparable age turned out to be mutually exclusive.Reports of pregnancy nausea were also taken. Previous suscept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

1971
1971
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(16 citation statements)
references
References 8 publications
1
13
0
Order By: Relevance
“…For this reason we wished to include questions additional to those concerning colds in the questionnaire. History of allergy seemed a good choice for inclusion because of the contradictory results obtained from earlier studies (Logan & Saker, 1955;Fisherman, 1960;Mackay, 1966;McKee et al, 1967;Ure, 1969;Shapiro et al, 1971;Gabriel et al, 1972;Meers, 1973;Alderson, 1974;Polednak, 1975;Allegra et al, 1976;Robinette & Fraumeni, 1978 analyses were repeated for the subset of cases and controls interviewed within 3 months of first diagnosis (81 cases and 145 controls); the results were similar to those reported in Table III. The relative risk of 6 found by Remy et al (1983) contrasts with our relative risk of 1.4.…”
supporting
confidence: 58%
See 1 more Smart Citation
“…For this reason we wished to include questions additional to those concerning colds in the questionnaire. History of allergy seemed a good choice for inclusion because of the contradictory results obtained from earlier studies (Logan & Saker, 1955;Fisherman, 1960;Mackay, 1966;McKee et al, 1967;Ure, 1969;Shapiro et al, 1971;Gabriel et al, 1972;Meers, 1973;Alderson, 1974;Polednak, 1975;Allegra et al, 1976;Robinette & Fraumeni, 1978 analyses were repeated for the subset of cases and controls interviewed within 3 months of first diagnosis (81 cases and 145 controls); the results were similar to those reported in Table III. The relative risk of 6 found by Remy et al (1983) contrasts with our relative risk of 1.4.…”
supporting
confidence: 58%
“…One other study may be methodologically sound (Allegra et al, 1976) and suggests a large negative effect although based on very small numbers; 1/74 cases and 13/86 controls had a history of allergy. The other studies, of which 5 find a statistically significant negative association (Fisherman, 1960;Mackay, 1966;Ure, 1969, Gabriel et al, 1972Meers, 1973) and one a significant positive association between history of allergy and cancer (Logan & Saker, 1955), are uninterpretable. Three cohort studies have looked specifically at asthma.…”
mentioning
confidence: 97%
“…70 The interest of the scientific community with regard to the biological consequences of this so-called "tumor allergy" on cancer progression was further stimulated when a negative correlation between atopy and cancer was first reported over 4 decades ago. [71][72][73] Subsequently, serum IgE levels and allergic reactions in the skin of cancer patients, 74,75 provided further evidence of a potential inverse relationship between allergy and cancer, and this seemed to be confirmed by the finding of a decreased prevalence of atopy in cancer patients. 76 In the early 1990s, the hypothesis that IgE antibodies possessed a natural surveillance function in malignancies was further fuelled when an immunohistochemical (IHC) study on the distribution of immunoglobulin classes in head and neck cancer revealed that IgE antibodies were the most abundant class.…”
Section: Allergooncology: Wielding the Allergic Response Against Cancermentioning
confidence: 99%
“…There is a long-standing interest in finding whether people with allergic disorders, such as hay fever, asthma, and eczema, have an increased or decreased risk of developing cancer [1][2][3][4][5]. Early papers largely reported inverse associations between a history of allergy or asthma and all-cancer risk [1,3], but others found little evidence of any association [4,5].…”
Section: Introductionmentioning
confidence: 99%